Exploring overlaps between the genomic and environmental determinants of LVH and stroke (2017)
Background: Whether left ventricular hypertrophy (LVH) is determined by similar genomic and environmental risk factors with stroke, or is simply an intermediate stroke marker, is unknown. Objectives: We present a research plan and preliminary findings to explore the overlap in the genomic and environmental determinants of LVH and stroke among Africans participating in the SIREN (Stroke Investigative Research and Education Network) study. Methods: SIREN is a transnational, multicenter study involving acute stroke patients and age-, ethnicity-, and sex-matched control subjects recruited from 9 sites in Ghana and Nigeria. Genomic and environmental risk factors and other relevant phenotypes for stroke and LVH are being collected and compared using standard techniques. Results: This preliminary analysis included only 725 stroke patients (mean age 59.1 13.2 years; 54.3% male). Fifty-five percent of the stroke subjects had LVH with greater proportion among women (51.6% vs. 48.4%; p < 0.001). Those with LVH were younger (57.9 12.8 vs. 60.6 13.4; p ¼ 0.006) and had higher mean systolic and diastolic blood pressure (167.1/99.5 mm Hg vs 151.7/90.6 mm Hg; p < 0.001). Uncontrolled blood pressure at presentation was prevalent in subjects with LVH (76.2% vs. 57.7%; p < 0.001). Significant independent predictors of LVH were age 90 mm Hg (AOR: 2.10; 95% CI: 1.39 to 3.19; p < 0.001). Conclusions: The prevalence of LVH was high among stroke patients especially the younger ones, suggesting a genetic component to LVH. Hypertension was a major modifiable risk factor for stroke as well as LVH. It is envisaged that the SIREN project will elucidate polygenic overlap (if present) between LVH and stroke among Africans, thereby defining the role of LVH as a putative intermediate cardiovascular phenotype and therapeutic target to inform interventions to reduce stroke risk in populations of African ancestry